Endothelin-1/Nitric Oxide Ratio as a Predictive Factor of Response to Therapy With Terlipressin and Albumin in Patients With Type-1 Hepatorenal Syndrome - Ahmed Abdel-Razik; Nasser Mousa; Mostafa Abdelsalam; Ahmed Abdelwahab; Mona Tawfik; Ahmed M. Tawfik; Ahmad S. Hasan; Rania Elhelaly; Niveen El-Wakeel; Waleed Eldars (Frontiers Media S.A., 2020)
Background and PurposePredictors of response to type-1 hepatorenal syndrome (HRS) therapy are urgently needed. This study's purpose is to evaluate the proposed predictors in these patients.MethodsForty-two type-1 HRS patients with cirrhosis were treated with albumin and terlipressin. Clinical, biochemical, and demographic parameters taken at the onset of therapy and changes in endothelin-1/nitric oxide (ET-1/NO) ratio during therapy were analyzed to check their predictive value.ResultsResponse to treatment (serum creatinine level <1.5 mg/dL at the end of therapy) was shown in 20 patients (48%). Independent predictive variables of response to therapy were early reduction of ET-1/NO ratio ≥0.15 at day 3 of therapy and serum bilirubin baseline <8 mg/dL (area under the receiver operating characteristic curve, 0.751; P < 0.001; specificity, 55%; sensitivity, 85%). Response rates in patients with serum bilirubin level <8 and ≥8 mg/dL were 63% and 20%, respectively (P = 0.008). The corresponding values in patients with an early reduction of ET-1/NO ratio ≥0.15 and <0.15 on day 3 were 85% and 13.6%, respectively (P < 0.001).ConclusionsEarly reduction of ET-1/NO ratio and lower serum bilirubin baseline can predict response to type-1 HRS therapy with albumin and terlipressin. Alternative therapy should be investigated for nonresponder type-1 HRS patients.